Peningkatan Kompetensi Profesionalisme Guru SD Dalam Pengembangan Desain Skenario Pembelajaran Berbasis Literasi Numerasi - Hadi, Samsul; Zaidah, Alpi (Lembaga Riset Ilmiah, 2023)
The purpose of this study was to describe the competence of elementary school teachers in developing a learning scenario design based on numeracy literacy. This research approach is a qualitative approach based on a case study with 21 primary school teachers participating in the 2021-2022 academic year, consisting of 9 female teachers and 12 male teachers. Data was collected by means of tests and non-tests (interviews, observations, questionnaires, and study documentation). The results of the study indicate that the ability of teachers to develop literacy-based learning designs is still low.